Content Validity of the Indonesian Version of the Carpal Tunnel Syndrome-6 (CTS-6) for the Assessment of Carpal Tunnel Syndrome - Jesisca Jesisca; Sekplin A. S. Sekeon; Seilly Y. Jehosua; Herlyani Khosama; Denny J. Ngantung (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The Carpal Tunnel Syndrome-6 (CTS-6) is a brief clinical scoring instrument used to assess the primary symptoms and signs of carpal tunnel syndrome (CTS). Before being used in Bahasa Indonesia, the instrument must undergo linguistic adaptation and content validity assessment to ensure that each item remains relevant and consistent with the clinical construct being measured. Objective: To develop the Indonesian version of the CTS-6 and evaluate its content validity. Methods: The adaptation process was conducted through forward translation, translation synthesis, expert content validity assessment, pretesting and discussion, backward translation, and finalization. Content validity was assessed by three neurologists using the Content Validity Index (CVI) with a 4-point relevance scale. Results: All six CTS-6 items received relevance ratings of 3 or 4 from all three experts. The Item-Level Content Validity Index (I-CVI) for all items was 1.00, while both the Scale-Level Content Validity Index based on the Average method (S-CVI/Ave) and the Scale-Level Content Validity Index based on Universal Agreement (S-CVI/UA) were 1.00. Editorial and operational revisions were made without altering the core concept of any item. Conclusion: The Indonesian version of the CTS-6 demonstrated excellent content validity and may serve as a foundation for the use of a concise clinical scoring instrument for assessing carpal tunnel syndrome. Further studies are needed to evaluate its reliability and other psychometric properties.